Three-dimensional evaluation of maxillary molar distalization with skeletal anchorage - Souza, Lorena Vilanova Freitas de (2020)
Introduction: This study aimed to evaluate the changes after maxillary molar distalization with direct skeletal anchorage, based on cephalometric superimposition of digital dental models evaluations and finite element analysis (FEA). Methods: The sample included 23 patients (9 males, 11 females; mean age 13.21 ±1.54 years) treated with the miniscrew anchored Cantilever and 26 patients treated by the First Class skeletally anchored First Class. Lateral cephalograms before and after molar distalization were evaluated with the Dolphin software. Superimposition of digital dental models using an open-source software was performed in Cantilever sample. FEA was performed to comparisons between buccal and palatal distalizing methods with skeletal anchorage. Results: In Cantilever sample, all maxillary teeth showed distal movement and palatal (incisors) or distal (posterior teeth) angulation showing statistically significance for the maxillary first premolar and maxillary first and second molars. The vertical changes were minimal. The first and second molars showed crown distal rotation of 19.31 ± 5.71º and 10.17 ± 3.84º, respectively. There was increase in intermolar distance. When Cantilever with direct skeletal anchorage was compared to First Class with indirect anchorage, the maxillary incisor showed palatal inclination (0.75 ± 2.57º) in the Cantilever group, and labial inclination (2.85 ± 3.53º) and protrusion (1.41 ± 1.40mm) in the First Class group. The maxillary first premolar showed distal angulation (4.15 ± 4.87º) and distal movement (1.09 ± 1.54mm) in the Cantilever group and mesial angulation (11.20 ± 24.19º) and mesial movement (2.62 ± 2.08mm) in the First Class group. Regarding FEA, tipping movements were predominant in first and second molars with both modalities, due to the higher displacements values at coronal levels than at apical regions. In the palatal appliance the palatal root showed slight greater displacement than in cantilever appliance, especially regarding distal movement. Conclusions: The miniscrew anchored cantilever was effective for maxillary molar distalization with minimal side effects. Three-dimensional displacement was observed for all teeth. Distal movement was progressively greater from anterior to posterior teeth. Both Cantilever and First Class appliances corrected the Class II molar relationship with similar molar distal angulation. Indirect anchorage does not provide absence of anchorage loss. The FEA showed predominantly tipping movements in both distalization methods and the von mises stress showed different patterns between appliances.